Optometry educators’ teaching experiences and opportunities pre-, during, and post-COVID-19 in South Africa - Metsing ,Thokozile Ingrid; Rasengane ,Tuwani Adelaide; Buthelezi ,Sanele (Taylor and Francis Group, 2024)
𝗔𝗶𝗺 The COVID-19 pandemic has impacted the higher education sector worldwide, and South Africa has faced unique challenges that continue to influence teaching beyond the pandemic. 𝗣𝘂𝗿𝗽𝗼𝘀𝗲 The study investigated the South African optometry educators’ teaching experiences and opportunities pre-, during, and post-COVID-19. 𝗠𝗲𝘁𝗵𝗼𝗱𝘀 The proposed study design was explorative and quantitative. Convenience sampling was used in recruiting participants. Optometry educators from four (4) universities training optometrists in South Africa were invited to participate in the study. An anonymous online questionnaire designed by the researchers was sent to participants to ensure that it captured relevant data. The questionnaire was sent electronically to the participants and SPSS was used to analyze collected data. 𝗥𝗲𝘀𝘂𝗹𝘁𝘀 Face-to-face (F2F) teaching was found to be the preferred method pre-COVID-19 by all participants. During the COVID-19 pandemic, the F2F was not the teaching method of choice due to safety measures put in place by the government. Online learning (OL) was preferred by 80% (n=4), and blended methods by 100%, due to flexibility in terms of lecture time allocation and digital device infrastructure. A statistically significant satisfaction was indicated by the academics before and post-COVID-19 pandemic with p=0.04 and p=0.02 respectively. The dissatisfaction related to online and blended methods of teaching used during the COVID-19 pandemic could be attributed to a lack of preparedness and digital device infrastructure. Beyond the COVID-19 pandemic participants raised concerns related to the lack of personal interaction and challenges of self-discipline required for online learning including face-to-face lectures. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻 Post the COVID-19 pandemic, there remains a need to address challenges related to the training of optometry educators in using online (OL) and blended methods (BM) of teaching, especially for those with more than 20 years of teaching experience. Whilst OL and BMs are beneficial, F2F teaching should not be neglected as it remains the cornerstone of effective education in optometry, especially in clinical training.
Keywords: Optometry education; Teaching methods; Blended learning; Hybrid teaching; Online teaching